Crop residues on short-term CO2 emissions in sugarcane production areas - Corradi, Mariana M. (2013)
The proper management of agricultural crop residues could produce benefits in a warmer, more drought-prone world. Field experiments were conducted in sugarcane production areas in the Southern Brazil to assess the influence of crop residues on the soil surface in short-term CO2 emissions. The study was carried out over a period of 50 days after establishing 6 plots with and without crop residues applied to the soil surface. The effects of sugarcane residues on CO2 emissions were immediate; the emissions from residue-covered plots with equivalent densities of 3 (D50) and 6 (D100) t ha-1 (dry mass) were less than those from non-covered plots (D0). Additionally, the covered fields had lower soil temperatures and higher soil moisture for most of the studied days, especially during the periods of drought. Total emissions were as high as 553.62 ± 47.20 g CO2 m-2, and as low as 384.69 ± 31.69 g CO2 m-2 in non-covered (D0) and covered plot with an equivalent density of 3 t ha-1 (D50), respectively. Our results indicate a significant reduction in CO2 emissions, indicating conservation of soil carbon over the short-term period following the application of sugarcane residues to the soil surface.